NETosis in Psoriatic Arthritis: Serum MPO–DNA Complex Level Correlates With Its Disease Activity - Li, Borui; Li, Guangtao; Yang, Xinlei; Song, Zhibo; Wang, Yu; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background NETosis has been rarely reported in psoriatic arthritis (PsA). We aimed to explore the involvement of NETosis in the inflammation of PsA. Methods Serum MPO-DNA complex was detected by a modified enzyme-linked immunosorbent assay (ELISA) and compared among 74 patients with PsA, 58 patients with psoriasis (PsO) and 20 healthy controls. The association of MPO-DNA level with disease activity index at baseline and follow-up was analyzed in PsA patients. Receiver operating characteristic curve was used to evaluate the predictive value of MPO-DNA for treatment response. Results MPO-DNA complex level in serum was significantly increased in PsA/PsO patients compared to healthy controls (p<0.001). The level of MPO-DNA was positively associated with DAPSA score and its components (including TJC, SJC, PGA, VAS-pain and CRP, r=0.25-0.409, all p-values<0.05). Serum MPO-DNA level was downregualted at 12-week after treatment compared to baseline (p=0.022). The decrease of MPO-DNA level was more dramatic in PsA patients who achieved both ACR50 and PASI50 response than those achieving neither of them at 12 weeks (p=0.023). ROC analysis revealed that the serum MPO-DNA level predicted both ACR50 and PASI50 achievement at week 12 (p=0.04, 95% CIs 0.56-0.94). Moreover, the baseline MPO-DNA level (p=0.009, 95% CIs 0.748-1) and change of MPO-DNA at week 12 from baseline (p=0.004, 95% CIs 0.802-1) were associated with the achievement of both ACR70 and PASI75 response at week 24. Conclusions NETosis plays an important role in psoriatic diseases. The level of MPO-DNA complex in serum reflects disease activity. Serum MPO-DNA complex may be a useful biomarker to predict the therapeutic response in PsA.